2016
DOI: 10.14740/jmc2386w
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of Esophageal Cancer: A Case Report and Review of Literature

Abstract: We present a case of a 49-year-old white female who complained of a chronic cough for 1 year. Computed tomography (CT) of the chest revealed abnormal thickening of the thoracic esophagus. Esophagogastroduodenoscopy (EGD) revealed diffuse multiple masses in the esophagus, which appeared separate. Histopathology of the masses revealed adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…showed that of 22 reported cases of ECs with unusual presentations, 6 cases presented with osteolytic lesions, 3 cases presented with cutaneous nodules, 2 cases with dyspnea, 2 cases with upper abdominal pain, and 1 case each with gluteal mass,[ 8 ] adrenal mass, thyroid mass,[ 9 ] headache with SOL, solitary jejunal mass, painful breast lump, hip pain, cervical pain, and chronic cough. [ 5 ] Of these 22 cases, 19 were metastatic ECs and only 3 cases were nonmetastatic cancer like our case. [ 5 ] Of the total 22 cases reported, only 5 cases had typical symptoms and the remaining 17 cases had atypical presenting symptoms.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…showed that of 22 reported cases of ECs with unusual presentations, 6 cases presented with osteolytic lesions, 3 cases presented with cutaneous nodules, 2 cases with dyspnea, 2 cases with upper abdominal pain, and 1 case each with gluteal mass,[ 8 ] adrenal mass, thyroid mass,[ 9 ] headache with SOL, solitary jejunal mass, painful breast lump, hip pain, cervical pain, and chronic cough. [ 5 ] Of these 22 cases, 19 were metastatic ECs and only 3 cases were nonmetastatic cancer like our case. [ 5 ] Of the total 22 cases reported, only 5 cases had typical symptoms and the remaining 17 cases had atypical presenting symptoms.…”
Section: Discussionmentioning
confidence: 81%
“…[ 5 ] Of these 22 cases, 19 were metastatic ECs and only 3 cases were nonmetastatic cancer like our case. [ 5 ] Of the total 22 cases reported, only 5 cases had typical symptoms and the remaining 17 cases had atypical presenting symptoms. [ 5 ]…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations